(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
The article discusses the artist’s artistic-aesthetic direction and stylistic skills based on the analysis of symbolic and figurative images in Khurshid Dostmuhammad’s short story “Kuza”.